COVID-19 Antibody Tests: A Valuable Public Health Tool with Limited Relevance to Individuals. Issue 3 (March 2021) - West, Rachel; Kobokovich, Amanda; Connell, Nancy; Gronvall, Gigi Kwik
Abstract : Antibody tests for detecting past infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have many uses for public health decision making, but demand has largely come from individual consumers. This review focuses on the individual relevance of antibody tests: their accuracy in detecting prior infection, what past SARS-CoV-2 infection can currently infer about future immunity or possible medical sequelae, and the potential future importance of antibody tests for vaccine selection and medical screening. Given uncertainty about the antibody tests (quality, accuracy level, positive predictive value) and what those tests might indicate immunologically (durability of antibodies and necessity for protection from reinfection), seropositive test results should not be used to inform individual decision making, and antibody testing should remain a tool of public health at this time. Highlights: There is high consumer demand for antibody tests to detect past infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but there is a great deal of uncertainty about what a positive test means immunologically. Uneven test accuracy and statistical challenges, especially in areas of low disease prevalence, further complicate use of antibody tests for individual decision making. Antibody tests are important for convalescent plasma donation and may have future utility to identify coronavirus disease 2019 medical sequelae and for vaccine selection and prioritization. At the population level, tests are needed to support serosurveillance studies, to determine the case fatality rate, and to track increases or decreases in incidence and prevalence, but currently they are of limited utility for individuals.